Skinfolds in 7 to 11 vears old school children - Hegg, Raymond Victor (Revista de Saúde Pública, 1978)
The correlation between two skinfolds of 717 caucasian Brazilian school children, 7 to 11 years old belonging to mediam high socio-economic group was analyzed. The medium values of both skinfolds showed marked and progressive increase, by age, for females and little change for males. Skinfold measures for females were higher than for males, significant at the 1% level. The triceps skinfold was higher than the subscapular skinfold for both sexes for all ages.